Village Voices '04 hopes and dreams - Price,Laurance (Tanzania Southern Pictures, 2010)
Village Voices was filmed on repeat annual visits to participating families who share their intimate perspectives on rural poverty and provide insights into forces that make it difficult to lift themselves out of poverty.
Keywords: Rural Poverty, Rural areas Families